Conservation should assume realistic adaptive capacities - Mark C. Urban; Chris S. Elphick; Daniel I. Bolnick (Proceedings of the National Academy of Sciences, 2026)
Conservation actions often assume implicitly that heritabilities are zero and that threatened populations cannot adapt to changing environments. To illustrate, we evaluated the last 10 y of recovery plans for US threatened and endangered species and found that only 4% assessed within-population adaptability. This omission reflects the common assumption that population adaptation is too slow or inconsequential to affect conservation practice in the short term. Yet, the median heritability (h 2 ) and evolvability (I A ) across many studies are not zero as assumed, but 0.3 and 0.4, respectively, based on a compilation of estimated values. This moderate heritability could rescue some populations. By compiling literature on conservation assessments, we detail how considering adaptability can shift conservation priorities, alter management recommendations, and provide additional ways to rescue declining populations and species. Based on these findings, we advocate for including population adaptability into conservation plans and adopting the prior expectation of moderate adaptability (h 2 = 0.3, I A = 0.4) along with its uncertainty, as a starting point when better information is lacking. This moderate adaptability could allow some species to respond naturally to environmental change while directing limited resources toward the species that need it most.